When Protection Becomes Persecution: Social Liability, Identity, and Democratic Decline in India - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2025)
In India, caste and religious affiliation have long served as pillars of social capital, offering protection, opportunity, and belonging. Yet when individuals defy social expectations—through interfaith marriage, conversion, or caste mobility—these same networks can become punitive. This paper explores the concept of social liability: the transformation of community ties into mechanisms of exclusion and harm. Drawing on sociological theory and anonymized case studies from recent expert witness reports, it illustrates how social capital turns against individuals who step outside prescribed roles. As Hindu nationalism rises, this reversal is increasingly reinforced by state policies, deepening the risks for religious and caste minorities. The consequences are not only personal but structural, contributing to migration, social fragmentation, and the erosion of democratic values. Understanding how belonging can become betrayal is essential to addressing India’s growing crisis of pluralism and to ensuring that community ties do not come at the cost of individual freedom.